An Educational Intervention to Increase Health Literacy Levels of Faculty of Health Sciences Students - Budak, Sümeyye; Özkan, Seçil (Turkey Health Literacy Journal, 2021)
Purpose: In this study, it is aimed to increase the level of health literacy of the students who are studying at the Faculty of Health Sciences and who will take place in different stages of health service provision in the future with educational intervention.Method: This study is an intervention study. Students of Ankara Gazi University Faculty of Health Sciences were given a 12-week face-to-face training within the sope of 2019-2020 Fall Period Health Literacy course. Pre and post-training health literacy levels were measured with Turkey Health Literacy Scale-32. The data were analyzed with the SPSS 23 program. Pre-test and post-test scores were compared using the Wilcoxon test. The statistical significance level was accepted as p
Keywords: Health Literac; Education; Intervention Study; Student; Faculty of Health Sciences